Locally forced convection in subkilometre‐scale simulations with the Unified Model and WRF. (16th August 2020) - Jucker, M.; Lane, T. P.; Vincent, C. L.; Webster, S.; Wales, S. A.; Louf, V.
Abstract: This study evaluates the performance and benefits of kilometre‐ and subkilometre‐scale convection‐permitting simulations over tropical Australia. Focusing on an extended monsoon break period, we can directly compare Unified Model (UM) and Weather Research and Forecasting model (WRF) simulations to C‐band polarimetric radar observations and soundings. We show that the two models have different behaviour, and both are different to observations. Whereas WRF produces daily squall lines whether or not they occurred in observations, the UM primarily generates small but intense storms. The UM and WRF produce qualitatively different surface density currents at different times in the diurnal cycle. Once the density currents are present, the models also show different behaviour in relation to convective initiation. While higher resolution helps in the distribution of total precipitation over the domain, most characteristics do not change with higher resolutions, and model differences are always larger than resolution differences. While Convective Available Potential Energy/Convective Inhibition (CAPE/CIN) does not seem to be important to explain model differences, our findings point to the evolution of density currents in the boundary layer as the most important source of model errors and differences. Abstract : Convection‐resolving models are the basis of weather forecasting but are also used to study the properties of convection where observations are not available. Further applications include studies of otherwise under‐resolved weather extremes, or to serve as "truth" for climate model validation and development of parametrizations. Here we show that these models can still be far from the truth, and much work still needs to be done to represent the involved physics accurately.